2015
DOI: 10.1111/jog.12826
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and survival analyses of synchronous primary endometrial and epithelial ovarian cancers

Abstract: In our cohort, we found that endometrioid/endometrioid type synchronous primary endometrial and ovarian cancer had different clinical histopathologic characteristics and favorable prognosis compared to the other histologic types of these cancers. Histopathologic type of the ovarian cancer component, stage of endometrial cancer and level of cancer antigen 125 at diagnosis were observed to have a great influence on the development of recurrence and survival of synchronous primary carcinomas of the endometrium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
3
18
0
3
Order By: Relevance
“…Several studies reported that women with synchronous EC and OC have a better overall prognosis than patients with a single-organ cancer with ovarian or endometrial spread [ 62 , 63 , 64 ]. The median 5-year disease-free survival (DFS) rate has been found to be 65% for synchronous EC and OC, while is less than 50% for stage IIIA of EC with ovarian spread [ 65 , 66 , 67 ]. The correct recognition of the synchronous or metastatic nature of EC and OC is pivotal in choosing the most suitable therapeutic strategies and requires extreme caution.…”
Section: Mitochondrial Dna Sequencing To Distinguish Simultaneous mentioning
confidence: 99%
“…Several studies reported that women with synchronous EC and OC have a better overall prognosis than patients with a single-organ cancer with ovarian or endometrial spread [ 62 , 63 , 64 ]. The median 5-year disease-free survival (DFS) rate has been found to be 65% for synchronous EC and OC, while is less than 50% for stage IIIA of EC with ovarian spread [ 65 , 66 , 67 ]. The correct recognition of the synchronous or metastatic nature of EC and OC is pivotal in choosing the most suitable therapeutic strategies and requires extreme caution.…”
Section: Mitochondrial Dna Sequencing To Distinguish Simultaneous mentioning
confidence: 99%
“…Clinical studies have reported associations between hyperplasia of ovarian stroma with increased androgen production by the ovaries, which also coincides with the development of hormonally related tumors, such as EC (4). In 10% of all women with OC and 5% of women with EC, the cancers of the endometrium and ovary coexist (5). Pathological changes in the endometrium can sometimes occur as a consequence of OC.…”
Section: Introductionmentioning
confidence: 99%
“…The mean ovarian tumour size was The 10-year disease-free survival rates were 92.9% for Group 1 and 84.6% for Group 2. As survival rates for Stage 1 OEC and SEOC alone have been reported in previous publications, survival data related to EOC and EOC with SEEC are given in Table 2 [3,[7][8][9]. Survival data were only retrieved from studies related to pure endometrioid histology.…”
Section: Resultsmentioning
confidence: 99%